Toward the definition of a novel response spectrum for the urban environment. Issue 143 (April 2021) - Tombari, A.; Cacciola, P.
Abstract: The earthquake motion at a given point on the surface is commonly represented by elastic response spectra. Seismic codes, however, do not distinguish between ground motion in a county side or within an urban environment. The traditional elastic response spectra are a function of seismological, geological, and geotechnical parameters and they are based on the prediction of the free-field motion at the ground surface, hence, by considering the propagation of the seismic waves in the soil deposit neglecting the presence of nearby buildings. During an earthquake a vibrating structure emanates waves travelling through the ground over large distances that modifies significantly the energy of the free-field seismic waves resulting in decrements of the ground motion energy in some areas and increments in others. In the urban environment, the vibrating buildings generate the occurrence of multiple interactions that are generally referred to as seismic site-city interaction. This paper presents a first attempt to quantify the impact of the urban environment on the commonly used elastic response spectrum defined at the free-field. A stochastic ground motion analytical model, able to capture the influence of the radiated wave field into the free field ground motion, is developed to determine novel elastic response spectra for urban areas. The proposed approach is verified through a pertinent Monte Carlo study. Moreover, a numerical model of a cluster of buildings is used to analyse the effect of the radiated waves from the ensemble of vibrating structures on the surrounding soil. Comparisons between the proposed and conventional elastic response spectra are carried out at selected locations. Remarkably, this paper shows the limitations of the traditionally used elastic response spectrum that might lead to an underestimation or overestimation of the seismic response of structures in the urban environment. Therefore, the proposed approach presents a promising strategy to predict accurately the seismic response in urban areas offering potential modifications to the current seismic code prescriptions. Highlights: Seismic ground motion is significantly altered by the presence of buildings in the urban environment. Impact of the Urban Environment has not yet considered in any seismic codes. A novel definition of response spectrum for the urban environment is developed. Deviations up to ±80–90% from the traditional elastic response spectrum are observed. A promising strategy to modify the current seismic code prescription is established.